Performance of Sharia Public Companies During the Covid-19: An Altman Z-Score Analysis - Didi Asmadi; Sri Rahmawati; Muhammad Ihsan (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This research aims to assess and analyze the financial performance of public companies operating under the Sharia category during the Covid-19 pandemic. The Altman Z-Score method, which utilizes four parameters and secondary data, was employed to investigate the 2020 financial statements of 30 companies listed in the Sharia category in JII. The study findings indicate that three companies exhibited potential bankruptcy as their Z-Score value was less than 1.1, while three other companies were susceptible to bankruptcy with a Z-Score value between 1.1 and 2.6. In contrast, 24 companies were classified as financially healthy since their Z-Score value was greater than 2.6. To mitigate the risk of bankruptcy, management is advised to implement effective debt restructuring and management strategies while examining best practices from companies that thrived during the pandemic. This research underscores the effectiveness of the Altman Z-Score method in assessing financial performance, identifying financial issues, predicting bankruptcy, and evaluating a company's financial health level.======================================================================================================== ABSTRAK – Kinerja Perusahaan Publik Syariah Pada Masa Pandemi Covid-19: Analisis Altman Z-Score. Penelitian in bertujuan untuk mengetahui dan menganalisis kinerja perusahaan terbuka kategori syariah pada masa pandemi Covid-19. Penelitian ini menggunakan metode Altman Z-Score dengan empat parameter dan data sekunder yaitu laporan keuangan tahunan perusahaan periode 2020, dengan sampel penelitian berjumlah 30 perusahaan terbuka kategori syariah dalam JII. Hasil penelitian menunjukkan 3 perusahaan berpotensi bangkrut karena nilai Z-Score kurang dari 1,1, dan 3 perusahaan berpotensi rawan bangkrut karena nilai Z-Score antara 1,1 dan 2,6, serta ada 24 perusahaan dalam kategori sehat karena Z-Score lebih dari 2,6. Untuk mengantisipasi potensi kebangkrutan, manajemen diharapkan dapat menerapkan strategi rekstrukturisasi manajemen dan utang serta melihat praktik baik perusahaan yang mampu bertahan dimasa pandemi. Penelitian ini juga menunjukkan bahwa metode Altman Z-Score mampu mengevaluasi kinerja, mendeteksi masalah keuangan, memprediksi kebangkrutan, dan dapat mengukur tingkat kesehatan keuangan perusahaan.